The King of Punjabi literature: Muhammad Asif Khan - Hussain, Fayyaz; Ahmad Sulehri, Iftikhar; Latif, Wasif (sourcecoder, 2022)
Muhammad Asif khan was well known Punjabi writer. His work covers many aspects of Punjabi literature. Being a linguistic, he worked on the different theories about the emergence of Punjabi language and mapped his own way. He edited various texts of prominent classical poets of Punjabi language. He served secretary of Pakistan Punjabi Adabi Board and edited Board’s Journal ’’Punjabi Adab" almost 24 years. Being a secretary of Board, he manages to publish more than one hundred and fifty books on Punjabi literature. Two books of his critic essays ’’Nik Suk’’, ’’Hor Nik Suk’’ have been published and more than one hundred research articles are still unpublished. Publication or compilation of these articles is the need of hour. In this article various aspects of Muhammad Asif Khan’s writings and his contributions of regarding Punjabi language and literature are discussed.